Life imprisonment a global human rights analysis - Van Zyl Smit, Dirk (Harvard University Press, 2018)
Life imprisonment has replaced capital punishment as the most common sentence imposed for heinous crimes worldwide. As a consequence, it has become the leading issue in international criminal justice reform. In the first global survey of prisoners serving life terms, Dirk van Zyl Smit and Catherine Appleton argue for a human rights-based reappraisal of this exceptionally harsh punishment. The authors estimate that nearly half a million people face life behind bars, and the number is growing as jurisdictions both abolish death sentences and impose life sentences more freely for crimes that would never have attracted capital punishment. Life Imprisonment explores this trend through systematic data collection and legal analysis, persuasively illustrated by detailed maps, charts, tables, and comprehensive statistical appendices. The central question--can life sentences be just?--is straightforward, but the answer is complicated by the vast range of penal practices that fall under the umbrella of life imprisonment. Van Zyl Smit and Appleton contend that life imprisonment without possibility of parole can never be just. While they have some sympathy for the jurisprudence of the European Court of Human Rights, they conclude that life imprisonment, in many of the ways it is implemented worldwide, infringes on the requirements of justice. They also examine the outliers--states that have no life imprisonment--to highlight the possibility of abolishing life sentences entirely. Life Imprisonment is an incomparable resource for lawyers, lawmakers, criminologists, policy scholars, and penal-reform advocates concerned with balancing justice and public safety.--